Downward price-based luxury brand line extension: Effects on premium luxury buyer's perception and consequences on buying intention and brand loyalty - Marcelo Royo-Vela; Mónica Pérez Sánchez (European Research on Management and Business Economics (ERMBE), 2022)
This research was carried out from the perspective of downward price-based brand extensions with the aim to discover its effects on customer perceptions regarding luxury brands and brand extensions and consequences on buying intention and luxury brand loyalty. The conceptual framework is based on both previous qualitative and quantitative research. A five factors model is tested in a judgemental sample of 158 premium luxury brands consumers using Partial Least Squares (PLS). Findings confirm that extension in new segments could negatively affect the brand concept perception of the parent luxury brand. These results indicate that (a) the brand concept consistency is affected by down-price brand extension, (b) due to brand concept changes then brand personality also changes, (c) this variations affect the fit between brand personality and consumer self-image and, (d), as a consequence, the purchase intention and brand loyalty are affected in a negative way. From a managerial point of view, this type of brand extension can be less positive than expected, generating negative effects against the extension and the parent brand itself. This work contributes to rethink the use of downward price-based brand extensions as an strategic alternative for brand managers.
Keywords: M37; M310; M370; 650; Brand concept consistency; Brand loyalty; Brand personality; Downward price-based brand extension; Luxury brand perception; Luxury consumer self-image congruency; Purchase intention